2011
DOI: 10.5194/bg-8-1865-2011
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotopes and lipid biomarker investigation of sources, transport and degradation of terrestrial organic matter in the Buor-Khaya Bay, SE Laptev Sea

Abstract: The world's largest continental shelf, the East Siberian Shelf Sea, receives substantial input of terrestrial organic carbon (terr-OC) from both large rivers and erosion of its coastline. Degradation of organic matter from thawing permafrost in the Arctic is likely to increase, potentially creating a positive feedback mechanism to climate warming. This study focuses on the Buor-Khaya Bay (SE Laptev Sea), an area with strong terr-OC input from both coastal erosion and the Lena river. To better understand the fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
120
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(141 citation statements)
references
References 50 publications
20
120
1
Order By: Relevance
“…Deep active-layer soils store large quantities of soil C (Mueller et al, 2015) but are not subject to abundant inputs of fresh C from vegetation. Therefore, the starting quality of the native soil C in active-layer soils is older, more microbially processed, and dominated by more stable "heavy" organic C (Karlsson et al, 2011). Thus, it may not be surprising that these more stable C compounds would be metabolized by processes that have been reported to be less temperature-sensitive.…”
Section: Temperature Vs Moisture Sensitivity For Cumulative Emissionsmentioning
confidence: 96%
“…Deep active-layer soils store large quantities of soil C (Mueller et al, 2015) but are not subject to abundant inputs of fresh C from vegetation. Therefore, the starting quality of the native soil C in active-layer soils is older, more microbially processed, and dominated by more stable "heavy" organic C (Karlsson et al, 2011). Thus, it may not be surprising that these more stable C compounds would be metabolized by processes that have been reported to be less temperature-sensitive.…”
Section: Temperature Vs Moisture Sensitivity For Cumulative Emissionsmentioning
confidence: 96%
“…4). Earlier studies demonstrated that the decay of fresh marine organic matter is more rapid compared to the degradation of terrestrial organic matter (Karlsson et al, 2011(Karlsson et al, , 2015Salvadó et al, 2016;Vonk et al, 2010). This may lead to the selective preservation of terrestrial organic matter in the sediments of the ESAS (Karlsson et al, 2011(Karlsson et al, , 2015Vonk et al, 2010).…”
Section: Dual-isotope-based Source Apportionment Of Ocmentioning
confidence: 99%
“…These different sources have a natural variability in their isotopic composition (endmembers). This variability needs to be taken into account to correctly estimate the relative source contributions and the associated uncertainties (e.g., Andersson, 2011). In previous studies a Bayesian Markov chain Monte Carlo (MCMC) approach has been used to estimate the relative source contributions for individual data points (Andersson et al, 2015;Tesi et al, 2016a).…”
Section: Source Apportionmentmentioning
confidence: 99%
“…The BKB is a hotspot for erosion input from coastal ice complexes (called "yedoma" by local people) and was reported to be an important region for land-seaatmosphere carbon exchanges (Semiletov, 1999a, b;Charkin et al, 2011;Karlsson et al, 2011;Semiletov et al, 2011). Erosion input stems from rapidly collapsing ice complexes, which compose up to 30 % of the BKB coastline.…”
Section: Study Areamentioning
confidence: 99%
“…POC represents an earlier phase of OM transformation associated with poorly defined compositional changes such as aggregation/disaggregation of particles, incorporation of older and more degraded material, and recombination of organic compounds (Cooper et al, 2005). In the BKB, major POC sources include soil and yedoma- borne terrestrial OC and OC mobilized to the water column by coastal and bottom erosion Karlsson et al, 2011;Feng et al, 2013).…”
Section: Biogeochemical Signatures Of Organic Matter Degradation In Smentioning
confidence: 99%